Exploring the Impact of Adverse Childhood Experiences on Self-Harm and Mental Health among Emerging Adults in Pakistan: A Mixed-Methods Study - Khan, Shukria Qasim (2024)
This study examined the frequency of Self-Harm Behavior (SHB) and determined the effect of ACEs on Self-Harm (SH) among Emerging Adults (EAs). This study reconnoitered how common ACEs are and how they instigate SHB among EAs in Pakistan. It involves a cultural adaptation of card sort task for self-harm (CaTS) followed by a pilot study to uncover the key pattern of SHB among EAs. The data for this study was collected through on-line google forms and in paper using simple random sampling from various local University settings. An analysis was conducted on 301 respondents out of 400 total samples, ranging in age from 18 to 29 years. The majority of the participants, 55.8%, were females, however for the SH variable, there was a significant difference observed between males and females, males reported SHB to a greater extent than females. A Bootstrapping analysis utilizing SMART PLS-SEM and linear regression model utilizing SPSS is conducted to determine the factors that predict SH among emerging adults. The study considered variables such as ACEs, Mental Health (MH), self-harm (SH), Social Functioning (SF) and Social Support (SS), while also accounting for other factors like socio-economic status, and family dynamics etc. Out of the 400, only 301 respondents were examined. According to the findings of the study, there was a significant increase in the likelihood of SH among EAs who experienced physical or sexual abuse, specifically; those with sexual abuse had a higher risk of having SHB, in comparison to those who did not experience abuse. The study demonstrates the negative inspiration of ACEs on SF. The output clearly explains the impact of ACEs on mental health (MH) and Self-harm (SH). It investigated the mediating role of social functioning (SF)between ACEs and MH. It explored the moderating role of social support (SS) that reduces the likelihood of SH among EAs. Conclusions imply that social support can foster favorable outcomes even for individuals from dysfunctional homes and that the protecting roles of SS grow with the number of support programs while this study depicted insignificant mediating role of MH between the ACEs and SH. This insignificance provides good evidence for the fact that SH is maladaptive coping during stressful situation and overcoming emotional dysregulation in EA. The study suggests that addressing MH and related emotion directive abilities right from the childhood can potentially impede forthcoming SHB, while also strengthening social support networks.